16.3k views
4 votes
D) p + 6pq - 2pq- 129
g) (2x - 3y) +b"(3y - 2x) + e- (2x - 3y)​

User Tomwilson
by
5.3k points

1 Answer

4 votes

d=

Let's simplify step-by-step.

p+6pq−2pq−129

=p+6pq+−2pq+−129

Combine Like Terms:

=p+6pq+−2pq+−129

=(6pq+−2pq)+(p)+(−129)

=4pq+p+−129

Answer:

=4pq+p−129

g=

Let's simplify step-by-step.

2x−3y+b(3y−2x)+2.718282−(2x−3y)

Distribute the Negative Sign:

=2x−3y+b(3y−2x)+2.718282+−1(2x−3y)

=2x+−3y+b(3y−2x)+2.718282+−1(2x)+−1(−3y)

=2x+−3y+b(3y−2x)+2.718282+−2x+3y

Distribute:

=2x+−3y+(b)(3y)+(b)(−2x)+2.718282+−2x+3y

=2x+−3y+3by+−2bx+2.718282+−2x+3y

Combine Like Terms:

=2x+−3y+3by+−2bx+2.718282+−2x+3y

=(−2bx)+(3by)+(2x+−2x)+(−3y+3y)+(2.718282)

=−2bx+3by+2.718282

Answer:

=−2bx+3by+2.718282

User Kvaruni
by
5.5k points